LB0002 The astis trial: Autologous stem cell transplantation versus IV pulse cyclophosphamide in poor prognosis systemic sclerosis, first results. (23rd January 2014) - van Laar, J.M.; Farge, D.; Sont, J.K.; Naraghi, K.; Marjanovic, Z.; Schuerwegh, A.J.; Vonk, M.; Matucci-Cerinic, M.; Voskuyl, A.E.; Tyndall, A.
Abstract : Background: Pilot studies have shown durable responses in two thirds of patients with poor prognosis diffuse cutaneous systemic sclerosis (dcSSc) treated with high dose immunosuppressive therapy and haematopoietic stem cell transplantation (HSCT), while a recent phase 2 randomised trial in 19 SSc patients showed superior benefit of HSCT over iv pulse cyclophosphamide on skin score and lung function [1-3]. HSCT has been further investigated in the ASTIS-trial (Autologous Stem cell Transplantation International Scleroderma trial), a prospective, controlled, randomized trial to compare safety and efficacy of HSCT versus iv cyclophosphamide in dcSSc patients at risk of major organ failure or early mortality. Objectives: To evaluate whether HSCT is superior over iv pulse cyclophosphamide in terms of safety and efficacy in dcSSc. Methods: Patients with early progressive dcSSc with or without major organ involvement were eligible. Patients randomized to the transplant arm underwent mobilization with cyclophosphamide 2x2 g/m 2 + G-CSF 10mcg/kg/d, conditioning with cyclophosphamide 200 mg/kg, rbATG 7.5 mg/kg, followed by reinfusion of CD34+ autologous HSCT. Those randomized to the control arm were treated with 12x monthly i.v. pulse cyclophosphamide 750 mg/m 2 . Crossing over was allowed after 2 years. Patients were seen at 3-monthly intervals for the first 2 years, and annually thereafter. The primary endpoint is event-free survival (EFS), defined as survival until death or development of major organ failure, at 2 yrs. Toxicity according to WHO criteria and progression-free survival are the main secondary endpoints, the latter captures predefined worsening of modified Rodnan skin score, functional ability, major organ function, and death. The effects of treatment are analysed on an ITT basis and by comparing EFS using the KM survival curves and by using the log-rank test. Results: One hundred fifty six patients were enrolled from March 2001 until October 2009 and randomised to either HSCT (n=79) or iv pulse cyclo (n=77). Seventy-five patients in each arm started treatment. Baseline characteristics of the patients were as follows: mean age 44 yrs, female 59%, mean disease duration 1.4 yrs, mean HAQ 1.35, prior cyclophosphamide therapy 22%, there were no significant differences between the 2 arms. With data cut at 1 March 2012, median follow ups (IR) are 33.0 (42.0) and 27.0 (34.0) months in the transplant and control groups respectively. Forty patients have died: 16 in the transplant group, 24 in the control group. Eight deaths in the transplant group were deemed treatment-related by the independent data monitoring committee, compatible with a 100d treatment-related mortality (TRM) of 10% (8/79). In the control group, none died from treatment-related causes and most deaths were due to progressive disease. Two additional patients in the transplant arm developed irreversible major organ failure (renal), while one additional patient in the control group became oxygen dependent. Seven patients in the control arm received rescue transplant treatment, one of whom died later from secondary acute myeloid leukaemia. None of the transplant patients were crossed over to the control arm. Conclusions: The ASTIS-trial is the first international, investigator-initiated, phase 3 stem cell transplant trial in early diffuse cutaneous systemic sclerosis. Initial results show fewer deaths in the transplant arm despite 100d TRM of 10%. HSCT should be considered as treatment option for patients with poor prognosis dcSSc. Further studies are needed to optimise the transplant regimen and patient selection. References: Vonk M et al. Ann Rheum Dis 2008;67:98-104. Nash R et al. Blood 2007;110:1388-96. Burt RK et al, Lancet 2011;378:498-506. Disclosure of Interest: None Declared